The Wiley-Blackwell handbook of positive psychological interventions - Parks, Acacia C. (Wiley-Blackwell, 2014)
Collating for the first time a range of techniques in positive psychology, this handbook introduces topics such as courage, empathy and humor, and spans areas as diverse as gratitude & forgiveness. It also explores special considerations such as ethics and motivation, and offers informed conjecture on future directions in research and practice.